PENGARUH INTEGRATED MARKETING COMMUNICATION TERHADAP BRAND EQUITY PADA SEBUAH BANK PEMERINTAH DI JAKARTA - AULIA DANIBRATA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2011)
The aim of the research was to gain a through knowledge of the variables influencing brand equity at state owned banks. The variable was marketing communication. It could be known the dimension shape the overall variables in relevance with assessment objectives and what the influence between variable is. Research methods used for this research were descriptive analysis which was used for qualitative variable, and verificative analysis consisted of hypothesis test by using statistical tests for causalities things. The analytical tool that being used is descriptive analysis for variables that are qualitative and verificative as hypothesis measurement by using statistic test analysis tools name structural equation model with Lisrel. The analytical units consist of the customers of the bank. The numbers of samples are 150 with random sampling techniques for the respondents. The research shown that of marketing communiction has significant influence on brand equity. It shown that in order to achieve high brand equity, the banks need to increase marketing communication.